Ziroom : creating quality rental living - Yu, Chungling; Mao, Chuanjiang ([London] : SAGE, 2016)
On 22 December 2013, in a Ziroom apartment located at the Overseas Chinese Town (OCT) in Beijing's Chaoyang District, Beijing Ziroom Youjia Property Asset Management Limited held its first-ever nostalgia-themed party, inviting more than 120 Ziroomers. The gathering began with Ziroom's 2013 annual feature film Forgive my peculiarity. In the film, Ziroomers from different places told their true stories in Beijing, sharing their varied work and living conditions, and different attitudes towards life. After that, Ziroomers gave performances, received awards, enjoyed food and took part in interactive games. Inspired by the anchor, the gathering had a heated active atmosphere. At the gathering, the hard work and happy lives of Beijing's young people in 2013, with 100,000 Ziroomers as representatives, were acknowledged. This case study examines this topic.
Originally Published in: Yu, C., & Mao, C. (2015). Ziroom: Creating Quality Rental Living. 8-114-311. Beijing: Tsinghua SEM China Business Case Center.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Marketing -- Management -- Case studies